Effect of the use of remineralization agents before resin infiltration on the treatment of initial enamel lesions: OCT, ultrasound, and SEM evaluation - MANAV, AYBİKE; DOĞU KAYA, BENGÜ; YILMAZ ATALI, PINAR; ALKAN, ELİF; TAĞTEKİN, DİLEK (My University, 2023)
Aim: It was aimed to investigate the effect of using remineralizing agent before resin infiltration application on the treatment of initial enamel lesions with OCT (Optical Coherence Tomography), Ultrasound and SEM (Scanning Electromicroscope). Materials and Methods: 80 enamel samples were kept in the demineralization solution (pH 4.5, 37°C) for 96 hours. Demineralized enamel samples will be randomly divided into 8 groups (n=10) including a remineralizing agent(Toothmousse/GC, Remin Pro/VOCO, Medical Mineral Gel/ROCS), resin infiltration (ICON/DMG), and a combined treatment of both. All remineralization agents were applied in remineralization cycle 2 times a day for 1 week.Measurements made from the enamel samples at the baseline, after demineralization and remineralization procedures evaluated with the OCT (Topcon3D OCT-1 Maestro) and ultrasonic system (Novascope 4500:NDT) lesion depths were measured. The sample surfaces were examined under SEM/EDS (Zeiss EVO-MA10) at x1000, 2500, 5000 and 10000. Data were analyzed in R program with WRS2. Two-way Robust Anova, Benferroni Test, and ICC (Intra-Class Correlation Coefficient) was used to examine the agreement between measurements. Significance level was set at p<0.05. Results: There was no statistical difference between the groups in OCT (p=0.884) and Ultrasound (p=0.051) median values after the protocols. In both measurement methods, the effect of remineralization treatments was statistically significant for lession depth (p<0.01). OCT median values were 104.01 in baseline, 144.78 in post-demineralization, and 90.5 in post-remineralization. Ultrasound median values were 1.34 in baseline, 1.1 in postdemineralization, and 2.36 inpost-remineralization. The highest ultrasound median value was obtained in the Remin Pro+ICON after remineralization (2.67), while the lowest value was obtained after demineralization (1.04). As a result of EDS analysis, the lowest Ca ratio (%atomic) was observed on the grup 5-ICON applied enamel surface (9.35). Conclusion: Although there is no significant difference between the groups, all groups were found efficient for remineralization treatments according to OCT, Ultrasound, and SEM/EDS analysis.
Keywords: remineralization; demineralization; resin infiltration technique; remineralization agent; pH cycle